Anti-infective Waste in a Pediatric Institution: Pinpointing Problems in the Process. (August 2020) - MacBrayne, Christine E.; Williams, Manon C.; Obermeier, Haley; Child, Jason; Heizer, Justin W.; Millard, Matt; Pearce, Kelly; Dugan, Casey; Parker, Sarah K.
Purpose: At Children's Hospital Colorado (CHCO), there are approximately 40 000 inpatient anti-infective orders every year resulting over 100 000 dispenses. Significant quantities of anti-infectives are wasted, incurring roughly $100 000 in waste annually. Identifying areas for improvement will result in cost savings and ameliorate the impact of drug shortages.Summary: This descriptive report discusses the reasons for anti-infective waste at a free-standing, quaternary-care, pediatric hospital. The anti-infectives with the highest cost in waste ($) included meropenem ($38 084), micafungin ($21 690), amphotericin B liposome ($15 913). An internal audit of CHCO anti-infective waste revealed that drugs are wasted for the following reasons: patient discharge, medication order discontinuation or change, and misplaced doses.Conclusion: The CHCO Antimicrobial Stewardship Program and the Pharmacy have proposed 4 process improvement measures that will target anti-infective waste to reduce pharmaceutical waste and hospital costs. These measures may be applicable to other drug classes that likely suffer from a similar proportion of waste.